LAW-JUSTIFYING AND LAW-NEGATING NORMS: HISTORY AND STRUCTURE - PAVLIUK, ANATOLII (Ehrlich’s Journal, 2023)
The article under studies deals with the issue of specific structuring of law-justifying and lawnegating norms in terms of historical-critical aspect. In other words, it describes the structure of the so-called basic legal norms (the norms that can either justify or negate recovery claims). The purpose of the article is to improve the structure of law-justifying and law-negating norms. In order to achieve the goal, it is necessary to fulfill the two tasks: first, to outline the history of the division of substantivelegal norms into law-justifying and law-negating ones, and second, to specify the structure of the three types of basic norms in terms of their historical-critical and dogmatic-critical interpretations. The article claims that the concept of basic norms (known implicitly to Roman lawyers) was explicated in the second half of the XIX century by B. Windscheid, as well as was applied in the German Civil Code. The absence of a legal definition for the concept of basic norms in the Ukrainian Civil Code or any other regulatory acts is not an obstacle to the use of this concept in the Ukrainian legal culture. The following elementary structure of a basic norm has been regarded in the article: A → Ch B, where A stands for the conditions for applying the norm, B means the content of the norm, i.e. the legal consequence, Ch means the nature of the legal norm, i.e. the nature of the relevant subjective right. In this structure, the subelements of A are α, β, γ, where α stands for law-justifying conditions of law, β means absolute law-negating conditions, and γ means relative law-negating conditions. The sub-elements of Ch are F, N, Fa, Na, Fr, Nr, whereby F stands for the foundation of a subjective right, N – for the negation of such a right, the r index is relational (relative), and the a index is absolute. The logical constants read: → – “if ..., then ... ” (implication), ∧ – “and” (conjunction), ¬ – “not” (negation of classical statement logic). It is proposed to structure basic legal norms as follows: a law-justifying norm may be reflected through three structures: (1) α → F B; (2) α ∧ ¬ β ∧ ¬ γ → Fa B; (3) α ∧ ¬ β ∧ γ → Fr B. Absolute law-negating norms will have the following structure: (4) α ∧ β → Na B, whereas relative law-negating norms will look like: (5) α ∧ ¬ β ∧ γ → Nr B. These formulas may be interpreted in the following way: law-justifying norms: (1) if the law-justifying conditions are fulfilled, the subjective right is deemed as justified; (2) if the law-justifying conditions are fulfilled, while the absolute and relative law-negating conditions are not fulfilled, the subjective right is deemed as absolutely justified; (3) if the law-justifying conditions are fulfilled, the absolute law-negating conditions are not fulfilled, and the relative law-negating conditions are also fulfilled, the subjective right is deemed as relatively justified. Absolute law-negating norms: (4) if both law-justifying, absolute and relative law-negating conditions are fulfilled, the subjective right is deemed as absolutely negated. Relative law-negating norms: (5) if the lawjustifying conditions are fulfilled, the absolute law-negating conditions are not fulfilled, and the relative lawnegating conditions are also fulfilled, the subjective right is deemed as relatively negated. It essential that (3) and (5) are different interpretations of the same norm. This means that relative negation is at the same time a relative justification of the norm. The article takes into account the fact that the relations between different forms of justification and negation are similar to those between alethic modalities in Clarence Lewis’ S5 system (necessity, possibility), supplemented by the concept of randomness: the relations between Fa,Naand Fr or Nr are of a contrary nature, whereas the relations between F and Na are of a contradictory nature, etc. It is of primary importance that the above-proposed formula is most efficient for structuring basic norms, since it relies on the concepts of justification and negation, as well as relativity and absoluteness. Its advantage is its relative simplicity compared to other structures. The structuring of basic norms, proposed in the article, can be applied within the framework of the reception and development of relational technique and the expertise style of processing a legal case.